No Shakespeare allowed - Jones, Robin D. (New York Atheneum, 1989)
As the daughter of the strong-willed director of her town's annual Shakespeare festival, fourteen-year-old Portia fears she can never escape theater, although she keeps trying to convince her stubborn father that she has no desire to become an actress.
Keywords: Theater -- Fiction; Fathers and daughters -- Fiction